2020
DOI: 10.46328/ijtes.v4i4.169
|View full text |Cite
|
Sign up to set email alerts
|

Moving from Face-to-Face to Remote Instruction in a Higher Education Institution during a Pandemic: Multiple Case Studies

Abstract: In response to the Covid-19 pandemic, our institution, like others in higher education, suspended face- to-face classes and offered remote learning as an alternative.  We report five cases of undergraduate and graduate courses that transitioned from a face-to-face to a remote mode. Each case will provide a detailed description of how the course was moved to an online mode, how the course was managed, the instructors’ previous experience in online teaching, their self-reflection on the process of transitioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…This is consistent with the results of this study and the results of our previous finding with a local sample of our own classes (Ghazi-Saidi et al 2020 ). Based on our findings, we argue that students’ evaluations are typically subjective rather than objective (i.e., with measurable outcomes).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the results of this study and the results of our previous finding with a local sample of our own classes (Ghazi-Saidi et al 2020 ). Based on our findings, we argue that students’ evaluations are typically subjective rather than objective (i.e., with measurable outcomes).…”
Section: Discussionsupporting
confidence: 94%
“…A relatively recent study has shown that interpersonal relationships in online environments are similar and correlated to face-to-face courses (Li et al 2018). Interpersonal relationships and strong communication were identified as important contributing factors for a successful face-to-face to online course transition during COVID-19 university shutdown (Ghazi-Saidi et al 2020 ). Many questions remain unanswered, however.…”
Section: Limitation Of This Study and Suggestions For Future Studiesmentioning
confidence: 99%
“…For this, we proposed problem-based learning strategies in questionnaires, elaboration of a scientific project and online quiz in order to complete the lectures. In the last few months, there has been a huge increase in the number of studies dedicated to developing and validating active learning strategies in remote or hybrid education, driven by the pandemic (Ghazi-Saidi et al, 2020; Hasnine and Ahmed, 2020; McGreevy and Church, 2020; Murugesan and Chidambaram, 2020; Qiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Educational institutions suddenly shifted from traditional learning to online education during the COVID-19 pandemic (Batmang et al, 2021;Scull et al, 2020;Xu, 2020). The new technological situation and disruptions that emerged with the effect of the pandemic situation (Ghazi-Saidi, 2020) have led to the aggravation of the learning-teaching tasks of music teachers and students, resulting in a rise in negative emotional characteristics. Many extra tasks that require time and patience of teachers and students have revealed many demands regarding their professional practices and competencies in this period.…”
Section: Introductionmentioning
confidence: 99%